Genome‐wide scan for runs of homozygosity in Asian wild boars and Anqing six‐end‐white pigs. (9th September 2022) - Wu, Xudong; Zhou, Ren; Wang, Yuanlang; Zhang, Wei; Zheng, Xianrui; Zhao, Guiying; Zhang, Xiaodong; Yin, Zongjun; Ding, Yueyun
Abstract: Inbreeding and loss of genetic diversity are serious problems in local Chinese pig breeds. Runs of homozygosity (ROHs) are contiguous lengths of homozygous genotypes that can provide information on inbreeding levels, mating schemes, selection pressure, and genetic events. The Anqing six‐end‐white (AQ) pig, an important autochthonous pig breed bred in the Anhui province of China, plays a key role in the local pig industry. In recent decades, AQ pigs have become a closed breed with a small population size in conservation farms, raising the issue of inbreeding decline. In this study, we used 10× resequencing to detect the whole genome of 24 AQ pigs and six Asian wild boars (AWBs). We used the Plink software to analyze the homozygosity of the genome and the distribution of ROHs in the genome based on the resequencing data. We obtained 935.04 Gb of raw data from the resequencing results and more than 45 822 239 SNPs. Additionally, we identified 28 702 ROHs. Compared with AWB, AQ pigs had higher ROH numbers, longer ROH rates, and higher F ROH values, which revealed that artificial selection influenced ROH distribution and genome inbreeding level. A total of 307 and 205 ROH islands were identified in the AQ pigs and AWBs respectively. The genes of ROH islands in AQ pigs were mainly enriched in immune biological processes. Our findings provide a useful reference for developing breeding programs to maintain genetic diversity and germplasm resources in AQ pigs.